The Concept of Poetry From Some Great Arab Poets' Perspectives - Al-Rawashdeh, Basma A. S.; Issa, Ahmad H. M. Bani; Al-Gayam, Ismeel M. M.; Rababah, Mahmoud Ali (Journal of language teaching and research, 2025)
At the beginning of the Renaissance, the phenomenon of writing introductions to poetry collections had spread among Arab poets. Remarkably, civilisational transformation played a prominent and stimulating role in the emergence of this phenomenon. The current study deals with six poets who wrote introductions to their collections in the book titled 'Introductions to the Arabic Poetry Collections' to express their sentiments and perspectives on 'the concept of poetry,' which had been renewed due to acculturation and direct contact between civilisations facilitated by the availability of means of communication and media development during their time. The six poets focused on in this study are Ahmed Faris Al-Shidiac, Sami Al-Baroodi, Ahmad Shawqi, Hafiz Ibrahim, Khaleel Motran, and Al-Zahawy. The study revealed that 'the concept of poetry' among these poets had not departed from its common definition within the old traditional framework. However, Al-Shidiac and Shawqi had direct contact with Western poets and modern criticism theories. Despite the various formulas and methods used to discuss this concept, it remained consistent with the definition of poetry provided by the old critics. Additionally, the results revealed a discrepancy between the level of theorising and views on the concept of poetry and the level of application and composition of poetry by the poets. For instance, the level of poetry theorising for Al-Shidiac and Al-Zahawy was higher than their level of poetic composition.